Measurement of the W boson polarisation in $$t\bar{t}$$ tt¯ events from pp collisions at $$\sqrt{s}$$ s = 8 TeV in the lepton + jets channel with ATLAS - M. Aaboud; G. Aad; B. Abbott; J. Abdallah; O. Abdinov; B. Abeloos; O. S. AbouZeid; N. L. Abraham; H. Abramowicz; H. Abreu; R. Abreu; Y. Abulaiti; et al. (European Physical Journal C: Particles and Fields, 2017)
Abstract This paper presents a measurement of the polarisation of W bosons from $$t\bar{t}$$ tt¯ decays, reconstructed in events with one high-$$p_{\text{ T }}$$ pT lepton and at least four jets. Data from pp collisions at the LHC were collected at $$\sqrt{s}$$ s = 8 TeV and correspond to an integrated luminosity of 20.2 fb$$^{-1}$$ -1 . The angle $$θ ^{*}$$ θ∗ between the b-quark from the top quark decay and a direct W boson decay product in the W boson rest frame is sensitive to the W boson polarisation. Two different W decay products are used as polarisation analysers: the charged lepton and the down-type quark for the leptonically and hadronically decaying W boson, respectively. The most precise measurement of the W boson polarisation via the distribution of $$\cos {θ ^{*}}$$ cosθ∗ is obtained using the leptonic analyser and events in which at least two of the jets are tagged as b-quark jets. The fitted fractions of longitudinal, left- and right-handed polarisation states are $$F_{0}=~0.709~± ~{0.019}$$ F0=0.709±0.019 , $$F_{L}=~0.299~± ~{0.015}$$ FL=0.299±0.015 and $$F_{R}=~-0.008~± ~{0.014}$$ FR=-0.008±0.014 , and are the most precisely measured W boson polarisation fractions to date. Limits on anomalous couplings of the Wtb vertex are set.